Regional Policy Coherence for the Great Green Wall Initiative: Maximising the flow and impact of finance - African Union (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Achieving the ambitious goals of the Great Green Wall Initiative (GGWI) requires unlocking and sustaining substantial financial resources to drive land restoration and climate resilience across Africa’s drylands. This policy brief examines the financial dimensions of the GGWI Strategy and Ten-Year Implementation Framework (2024–2034), highlighting key challenges and opportunities for enhancing funding mobilisation, financial governance, and investment impact. The GGWI Strategy prioritises regional policy coherence as a means to improve access to diverse funding streams, reduce inefficiencies, and bolster the initiative’s investment appeal. Strategic alignment with complementary African Union frameworks - such as the Green Recovery Action Plan (GRAP), Climate Change and Resilient Development Strategy (CCRDS), Biodiversity Strategy and Action Plan (ABSAP), and the Sustainable Forest Management Framework (SFMF) - enhances synergies and opens avenues for blended finance, green bonds, and payments for ecosystem services. Robust monitoring, reporting, and verification systems, including digital and satellite-based tools, are central to unlocking results-based climate finance. Furthermore, dedicated financial instruments for women- and youth-led enterprises, Environmental, Social, and Governance (ESG) aligned investment standards, and expanded private sector participation are critical for inclusive financing. The brief also emphasises the importance of strengthening subnational financial capacities, improving domestic resource mobilisation, and aligning GGWI implementation with macroeconomic and nature-positive financial reforms. By fostering innovation in finance, enhancing governance readiness, and aligning with regional and global frameworks, the GGWI can scale up sustainable investment and accelerate the restoration of degraded landscapes. This financial transformation is key to delivering climate resilience, biodiversity conservation, and improved livelihoods across Africa.